2002
DOI: 10.1152/ajpheart.00274.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanics of mouse cardiac myosin isoforms

Abstract: Two myosin isoforms are expressed in myocardium, alphaalpha-homodimers (V(1)) and betabeta-homodimers (V(3)). V(1) exhibits higher velocities and myofibrillar ATPase activities compared with V(3). We also observed this for cardiac myosin from normal (V(1)) and propylthiouracil-treated (V(3)) mice. Actin velocity in a motility assay (V(actin)) over V(1) myosin was twice that of V(3) as was the myofibrillar ATPase. Myosin's average force (F(avg)) was similar for V(1) and V(3). Comparing V(actin) and F(avg) acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
97
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 53 publications
10
97
1
1
Order By: Relevance
“…Single molecule studies have also demonstrated that the higher actin sliding velocity of the αMHC isoform is related to a shorter attachment time of myosin after the power stroke and not to the displacement generated by the myosin power stroke [29,30]. These studies have suggested that the kinetics (attachment time) rather than the mechanics (unitary displacement) of the myosin molecule accounts for the difference in the actin-sliding velocity of the α and βMHC isoforms [23,[28][29][30]. Based on these observations, it is generally believed that hearts expressing primarily αMHC isoform have a significantly higher velocity of muscle shortening; whereas hearts expressing mostly βMHC, which has low ATPase activity, have the ability to generate force with greater economy.…”
Section: Functional Consequences Of Myosin Isoform Shiftmentioning
confidence: 99%
See 4 more Smart Citations
“…Single molecule studies have also demonstrated that the higher actin sliding velocity of the αMHC isoform is related to a shorter attachment time of myosin after the power stroke and not to the displacement generated by the myosin power stroke [29,30]. These studies have suggested that the kinetics (attachment time) rather than the mechanics (unitary displacement) of the myosin molecule accounts for the difference in the actin-sliding velocity of the α and βMHC isoforms [23,[28][29][30]. Based on these observations, it is generally believed that hearts expressing primarily αMHC isoform have a significantly higher velocity of muscle shortening; whereas hearts expressing mostly βMHC, which has low ATPase activity, have the ability to generate force with greater economy.…”
Section: Functional Consequences Of Myosin Isoform Shiftmentioning
confidence: 99%
“…The mechanical properties of the heart are well correlated with the type of MHC isoform expressed [23]. Studies conducted on myofibrillar ATPase activity have documented that the speed with which muscle shortens (the velocity of shortening) is correlated with the ATPhydrolyzing capacity of the myosin molecule [24].…”
Section: Functional Consequences Of Myosin Isoform Shiftmentioning
confidence: 99%
See 3 more Smart Citations